Tuberculosis-Associated Hemophagocytic Lymphohistiocytosis in a Tertiary Hospital in the Philippines: A Case Series and Review of Literature - L Balane, Janika Adrienne; A Guiao, Patrick Neil; Ato, Benjo P; B Bagsic, Chryz Angelo Jonathan; A Pacana, Desiree Joy; G Gana, Jose Emmanuel; R Natividad, Ana Margarita; Poblete, Jonnel B; G Casanova, Dondiego Eleazar; V Gauiran, Deonne Thaddeus (Global Journal of Medical and Clinical Case Reports, 2025)
Background and objectives: Hemophagocytic Lymphohistiocytosis (HLH) is a life-threatening hyperinflammatory syndrome characterized by uncontrolled immune activation leading to multiorgan dysfunction. It poses significant diagnostic and therapeutic challenges due to its nonspecific presentation and overlap with other systemic diseases. Among infectious triggers, Mycobacterium Tuberculosis (MTB)—endemic in the Philippines—remains a rare but serious cause of secondary HLH. This report aims to describe the clinical presentation, diagnostic challenges, management, and outcomes of patients diagnosed with Tuberculosis-Associated HLH (TB-HLH) in a tertiary hospital in the Philippines. Methods/Case Summary: We report four adult cases of HLH secondary to confirmed MTB infection. Three of four patients met the HLH-2004 diagnostic criteria, all had a high Hscore, and TB was identified through microbiologic, molecular, or histopathologic evidence. Clinical features, laboratory findings, treatment regimens, and outcomes were reviewed. Discussion and Conclusion: Patients presented with prolonged fever, cytopenia, unexplained hepatosplenomegaly, and elevated inflammatory markers. Diagnosis was often delayed due to overlapping features of disseminated TB and HLH. The patients received concurrent Anti-Tuberculosis Therapy (ATT) and immunomodulatory treatment, with variable clinical responses and outcomes. TB-HLH represents a diagnostic and therapeutic emergency that requires early recognition and simultaneous management of both the infection and the hyperinflammatory response. In endemic settings such as the Philippines, clinicians should maintain a high index of suspicion for HLH in patients with severe or disseminated TB. This report presents, to our knowledge, the first documented case series of TB-HLH in the country, underscoring the need for increased awareness and multidisciplinary care.